Innovative Learning Strategies and the Role of Teacher Professionalism in Improving the Quality of Education - Tisar Dewi Pratiwi (Gateway for Understanding Research in Education, 2025)
Education is a key pillar in developing quality human resources. To meet the demands of the 21st century, innovative learning strategies and teacher professionalism are essential in creating effective and meaningful learning. This study aims to analyze the impact of innovative learning strategies and teacher professionalism on improving education quality in secondary schools. Using a quantitative approach with a correlational descriptive design, data were collected through questionnaires from 50 junior and senior high school teachers in Padang. Variables include the types of innovative strategies used, indicators of teacher professionalism (pedagogic, personality, social, and professional competencies), and indicators of educational quality such as learning outcomes and student motivation. Pearson correlation and multiple linear regression were used for data analysis. The findings indicate a positive and significant correlation between innovative strategies and teacher professionalism with improved education quality (p < 0.05). Strategies like project-based learning, interactive approaches, and digital collaboration tools increase student engagement and outcomes. Teacher professionalism supports consistency and effectiveness in the learning process. The study highlights the need for ongoing teacher training to align strategies with current educational demands and strengthen professional competence. Conclusion: A strong synergy between innovative learning strategies and teacher professionalism is vital for fostering adaptive and sustainable education quality.